Quasi-Soft Variable Structure Control of Discrete-Time Systems With Input Saturation - Ignaciuk, Przemyslaw; Morawski, Michal (IEEE transactions on control systems technology, 2019)
In the effort to improve the convergence rate of linear controllers, at the same time avoiding abrupt input transitions and implementation difficulties of time-optimal ones, soft variable structure control (VSC) may be considered. The classical formulation of soft VSC in continuous time domain assumes smooth, yet instantaneous switching in an infinite pool of controllers, which is not possible in the now commonplace digital control schemes. In discrete-time systems, the control structure may be changed only at the sampling instants, which results at best in quasi-soft behavior. This brief presents a design of quasi-soft VSC system, which by directly covering the discretization effects, permits maintaining the favorable properties of fast convergence and smooth inputs in discrete time domain, thus bringing the realization of soft VSC closer to the industrial reality. The properties of the presented control system are formally proved and verified experimentally.